(untitled) (Journal of Partial Differential Equations, 2024)
This paper is devoted to establishing the Adams-Onofri inequality with logarithmic weight for the second order radial Sobolev space defined on the unit ball in R^4. By using this inequality we obtain the existence of solutions for mean field biharmonic equation with logarithmic weight.